Assessment of quality-of-life in patients with face-and-neck burns: The Burn-Specific Health Scale for Face and Neck (BSHS-FN). Issue 6 (September 2018) - Gandolfi, S.; Carloni, R.; Bertheuil, N.; Grolleau, J.L.; Auquit-Auckbur, I.; Chaput, B.
Highlights: Quality of life of patients with burns at the cephalic level was evaluated with a new created scale: The Burn Specific Health Scale for Face and Neck. After construction of the BSHS-FN, we compared QoL of patients with or without face-and-neck burns. SF-36, BSHS-B, BSHS-FN questionnaires were delivered by an interview to 53 patients divided in two groups (General burns and Face and Neck burns). A sub-group of patients with face and neck burns was evaluated through the BSHS-B and BSHS-FN, both before and after 6 months of a reparative surgery. Scores from different domains of the three questionnaires were calculated as percentage ratios between the total scores of the related items and the maximum score for the related domain. Comparisons between the two groups of patients were performed using the Mann–Whitney U test. Results show that the BSHS-FN, is significantly more sensitive to assess the QoL of patients with face-and-neck burns supporting its application in routine clinical. Abstract: Introduction: Burns to the cephalic extremities are particularly implicated in problems of self-image and alterations to personal social relations. The aim of this study was to objectively assess the quality-of-life (QoL) of patients suffering from face-and-neck burns through our newly created scale: The Burn-Specific Health Scale for Face and Neck (BSHS-FN). Methods: After constructing the BSHS-FN, we compared QoL of patients with or without face-and-neck burns. SF-36, the French version of the BSHS-B (Burn Specific Health Scale-Brief), and the BSHS-FN were administrated to 53 patients divided into two groups: GB group (general burns, 26 patients) and FN group (face-neck burns, 27 patients). Results: QoL evaluated using the SF-36 had a higher average total score in GB patients compared to FN patients, but there were no significant difference between the two groups (54.3 ± 18.5 vs. 47.0 ± 17.3, respectively, p  = 0.11). In contrast, in BSHS-B the total score was significantly different between the two groups with a higher score recorded for the GB group (71.9 ± 13.4 [median: 72.8] in the GB group vs. 62.2 ± 14.4 [median: 64.4] in the FN group). In percentage terms, total score of BSHS-FN for GB group was 79.1 ± 10.1, while total score for FN group was 53.6 ± 13.1 ( p  < 0.001), with the highest score for the Face and Neck domain in GB group (99.7 ± 1.1, p  < 0.001) Conclusion: The BSHS-FN seemed to be more appropriate to assess QoL for FN burn patients. This study supports its application in routine clinical practice and in international studies.